(untitled) (Comprehensive Journal of Science, 2026)
This qualitative study explores the lived perspectives of English language instructors on teaching English morphology within the context of Libyan higher education. Conducted at the College of Education – Ajaylat, University of Al‑Zawiya with a purposive sample of 15 faculty members, the research investigates instructional strategies, perceived challenges, and contextual factors that shape morphological instruction. Data were gathered through semi‑structured interviews and analyzed thematically to highlight local pedagogical realities. Findings reveal a strong recognition among instructors of the importance of morphology for vocabulary and language competency, yet manifest contextual constraints including limited instructional time, heavy curricula, and alignment with student linguistic backgrounds. Results are presented through descriptive tables and narrative themes. Based on these findings, the study proposes context‑specific implications for curriculum design and teacher development that address morphology instruction more effectively in Libyan universities.